Examining and Testing a Model for Attracting Knowledge Workers Based on Professional Competencies (Case Study: Governmental Organizations in Iraq) - Mohsin AlRashid, Faten Abed; Aghababaei Dehaghani, Zohreh; Badrawi Alkhammas, Abdulridha Faraj; Shariati Kamalabadi, Mohsen (Assessment and Practice in Educational Sciences, 2025)
Knowledge workers possess advanced education, high technical literacy, and elevated cognitive abilities, including abstract reasoning. They also demonstrate the capacity to observe, integrate, and interpret data and information while generating and transferring new perspectives and insights that support improved decision-making and more appropriate organizational solutions. The present study aims to examine and test a model for attracting knowledge workers based on professional competencies in the context of governmental organizations in Iraq. Accordingly, the research is applied in purpose, quantitative in data type, and descriptive–correlational in method. The statistical population consists of managers and officials from various governmental organizations. Due to the unlimited size of the population, Cochran’s formula for an infinite population was applied, resulting in a sample size of 384 individuals. The research instrument was a questionnaire, and data analysis was conducted using structural equation modeling (SEM) in PLS software. The results indicate that all hypothesized relationships were confirmed (t-value > 1.96). The model fit index reached 0.63, indicating a strong model fit. Furthermore, the factor loadings for all components exceeded 0.40, confirming the acceptability of the confirmatory factor analysis.